Systematics of Anopheles barbirostris van der Wulp and a sibling species of the Barbirostris Complex (Diptera: Culicidae) in eastern Java, Indonesia. (17th January 2013) - TOWNSON, HAROLD; DYER, NAOMI; MCALISTER, ERICA; SATOTO, TRI BASKORO T.; BANGS, MICHAEL J.; HARBACH, RALPH E.
Abstract : This study provides the first integrated morphological and molecular characterization of Anopheles barbirostris van der Wulp, the nominotypical member of the Barbirostris Complex of malaria vectors in the Oriental Region, and An. vanderwulpi sp.n., a sibling species of the complex found in sympatry with An. barbirostris in the vicinity of its type locality in eastern Java, Indonesia. The adult, larval and pupal stages of An. barbirostris are described and compared with those of An. vanderwulpi . The two species, however, are essentially isomorphic. The genetic identity of An. barbirostris s.s. is based on a diagnostic cytochrome oxidase I gene sequence to ensure stable use of the specific name for the prevalent concept of the species. The genetic identity of the new species is also established. Diagnostic DNA sequences for these species serve as a foundation for further taxonomic studies, and for investigations into their roles in the transmission of malaria and filariasis. The discussion includes a brief review of Anopheles classification and species complexes.